Network Coverage: Administrative Collegiality and School District Ethos in High-Performing Districts - Coleman, Peter; Mikkelson, Lorna; LaRocque, Linda (Canadian Journal of Education/Revue canadienne de l'éducation, 1991)
We interviewed administrators in two high- and two low-performing school dist- ricts in British Columbia to see if interactions between district- and school-based administrators (and interactions within the latter group) would distinguish between these pairs of districts. We asked if administrator collegiality would characterize the first pair but not the second. Respondents in high-performing districts often referred to their satisfying pro- fessional relationships with colleagues. Respondents in low-performing districts barely mentioned collegial contact except where principals thought they had to present a united front against district policy threatening their “turf.” In high-per- forming school districts, collegiality included issues of school improvement. Superintendents act like effective principals—they create an “associative” climate at district level in which climate “district-regarding principals” seek the greater good. There is greater similarity in district interaction patterns within the two per- formance groups than there are sharp distinctions between them. Nous avons interviewé, en Colombie-Britannique, des administrateurs de quatre circonscriptions scolaires—deux à faible rendement et deux à rendement élevé— afin de vérifier si les interactions des administrateurs des circonscriptions et des écoles (et des administrateurs d’école entre eux) se distinguaient selon les deux paires de circonscriptions. Nous cherchions à savoir s’il y existait, dans la pre- mière paire, une collégialité chez les adminstrateurs, qui serait absente dans la seconde. Les répondants dans les circonscriptions scolaires à haut rendement ont sou- vent fait allusion aux relations professionnelles satisfaisantes qu’ils entretenaient avec leurs collègues. Ceux des circonscriptions scolaires à faible rendement ont à peine fait mention des contacts avec leurs collègues, à l’exception des direc- teurs d’école qui estimaient devoir faire front commun contre les politiques des circonscriptions menaçant leur “territoire.” Dans les circonscriptions scolaires à haut rendement, les questions ayant trait à l’amélioration de l’école étaient asso- ciées à la notion de collégialité. Les administrateurs en chef agissent comme le font des directeurs d’école efficaces: ils créent, au niveau de la circonscription, un climat tel que les directeurs d’école cherchent ce qui contribue davantage au bien de la circonscription. Il y a plus de similitudes que de grandes différences entre les types d’interac- tion au sein des deux groupes de circonscriptions.